Horizontal distributions of sprites derived from the JEM‐GLIMS nadir observations. Issue 7 (8th April 2016) - Sato, M.; Mihara, M.; Adachi, T.; Ushio, T.; Morimoto, T.; Kikuchi, M.; Kikuchi, H.; Suzuki, M.; Yamazaki, A.; Takahashi, Y.; Inan, U.; Linscott, I.; et al.
Abstract: Global Lightning and Sprite Measurements on Japanese Experiment Module (JEM‐GLIMS) started the nadir observations of lightning discharges and transient luminous events (TLEs) from the International Space Station (ISS) since November 2012. In the nadir observations, JEM‐GLIMS optical instruments have to simultaneously detect incomparably intense lightning emissions and weak TLE emissions. To distinguish TLEs, especially sprite events, from lightning events, combined data analytical methods are adopted: (1) a subtraction of the wideband camera image from the narrowband camera image, (2) a calculation of the intensity ratio between different photometer channels, and (3) an estimation of the polarization and charge moment changes for the TLE‐producing lightning discharges. We succeeded in identifying numbers of sprite events using the combined analytical methods, and here we report three sprite events detected by JEM‐GLIMS as a case study. In the subtracted images, sprite emissions are located over the area of the sprite‐producing lightning emissions. However, these sprites and sprite‐producing lightning discharges did not occur at the nadir point of the ISS. For this reason, the geometry conversion of the sprite and sprite‐producing lightning emissions as observed from the point just over the sprite‐producing lightning discharges is performed. In the geometry‐converted images, the locations of the sprite emissions are clearly displaced by 8–20 km from the peak positions of the sprite‐producing lightning emissions. Thus, the first quantitative spatial distributions of sprites and sprite‐producing lightning discharges from the JEM‐GLIMS nadir observations are revealed. Key Points: Data processing techniques are introduced to distinguish sprite emissions from lightning emissions The locations of sprite emissions are displaced by 8–20 km from the parent lightning emissions The quantitative spatial distributions of sprites are derived from the JEM‐GLIMS nadir observations